Expectativas socialmente construídas: fundamentos, formalização e resultados exploratórios - Camargos, Luiz Rogério de (2006)
This thesis is a critical discussion, under the light of expectation formation, of the relation that interposes between economic science as body of knowledge and its agents. First, we examine significant approaches of expectation formation currently used in economic analysis, indicating its insufficiencies. We argue that the incorporation of expectation, in any analytical treatment, must involve, mainly, epistemic basis. Second, under the perspective of the reflexive modernity theory developed by Anthony Giddens, we search to identify plausible basis for a theory of economic expectation. We argue that the process of expectation formation is a social construction derived from the interdependence between experts and laypeople. We call this conclusion by hypothesis of socially constructed expectation (HESC). Third, we propose an analytical framework to incorporate the HESC. Basically, expectation information spreads out through media and by face to face interactions between agents. New information does not necessarily mean expectation update, but it goes to mainly depend on economic knowledge and neighborhood of the agent. For last, an application example: the model-HESC was submitted to three macroeconomic experiments, comparing its results with those gotten by Mankiw and Reis (2002). Although the similarities, there are significant differences. The first conclusion of this thesis is methodological: expectations of the agents in macroeconomic models are not determined from equations of the model. The second is normative: knowledge and neighborhood are able to perpetuate inefficiencies due to errors of expectations. The third concerns with positive economics: the differences between the results gotten in the model of information-rigid of the authors above and those in the model-HESC point with respect to new explanatory possibilities.